Histopathological study of the Influence of Estradiol on Liver Regeneration in Male Rabbit - K., Mahdi A. (The Iraqi Journal of Veterinary Medicine, 2013)
This study was investigated to recognize the generative capacity of liver that influenced by administration of estradiole benzoate. Twenty four healthy local breed male rabbits weighed 1.5-2 kg were used .They were classified into two equal groups control and treated groups. Animals anaesthetized by intramuscular injection of Ketamine (35mg /kg B.W) and Xylazine (5mg\kg B.W.) In control group partial hepatectomy of liver was done, while in treated animals were subject to a same operation then received an intramuscular injection 0.1ml of estradiol benzoate 0.2% at 3rd and 5th days post operation. At 3rd days microscopic finding showed biopsy were taken at 3rd, 7th and 14 day, post operation to study the histopathological changes in liver regeneration .At 3rd day it showed early proliferation of hepatocyte character by irregular hyperchromatic multinucleated cell .While in control group it showed necrotic area of liver parenchyma surrounded by thick fibrous connective tissue infiltrated with inflammatory cells. At 7th day in treated animals still progress in proliferation of hepatocyte while, liver proliferation phase showed in control group .At 14th day in treated animals showed large cells of hepatocyte with double nuclei aggregation without central vein , while in control group showed small hyperchromatic hepatocyte with present of necrotic area. In conclusion the results of this study indicate that administration of estrogen after partial resection in male rabbits has a role in liver regeneration by early initiate or facilitate heypatocyte proliferation.